The All-Sky Automated Survey for Supernovae (ASAS-SN) Light Curve Server v1.0. (24th August 2017) - Kochanek, C. S.; Shappee, B. J.; Stanek, K. Z.; Holoien, T. W.-S.; Thompson, Todd A.; Prieto, J. L.; Dong, Subo; Shields, J. V.; Will, D.; Britt, C.; Perzanowski, D.; Pojmański, G.
Abstract: The All-Sky Automated Survey for Supernovae (ASAS-SN) is working toward imaging the entire visible sky every night to a depth of V ∼ 17 mag. The present data covers the sky and spans ∼2–5 years with ∼100–400 epochs of observation. The data should contain some ∼1 million variable sources, and the ultimate goal is to have a database of these observations publicly accessible. We describe here a first step, a simple but unprecedented web interfacehttps://asas-sn.osu.edu/ that provides an up to date aperture photometry light curve for any user-selected sky coordinate. The V band photometry is obtained using a two-pixel (16.″0) radius aperture and is calibrated against the APASS catalog. Because the light curves are produced in real time, this web tool is relatively slow and can only be used for small samples of objects. However, it also imposes no selection bias on the part of the ASAS-SN team, allowing the user to obtain a light curve for any point on the celestial sphere. We present the tool, describe its capabilities, limitations, and known issues, and provide a few illustrative examples.